Barkhausen noise emission of AISI 304 stainless steel originating from strain induced martensite by shot peening - M. Neslušan; P. Minárik; R. Čep; J. Uríček; K. Trojan; N. Ganev; L. Trško (Journal of Materials Research and Technology, 2022)
This study deals with magnetic Barkhausen noise emission produced by strain-induced martensite generated during shot peening of austenitic AISI 304 stainless steel. The transformation from the paramagnetic to ferromagnetic state and the corresponding birth of the magnetic domain structure are important with respect to irreversible motion of domain walls and the corresponding Barkhausen noise emission. Barkhausen noise is investigated and explained with respect to the residual stress state as well as the microstructure expressed in terms of the martensite fraction, its crystallite size, preferred orientation, surface topography, and microhardness. The strength of the Barkhausen noise is mainly linked with the number of shot peening cycles, corresponding Almen intensity, and the associated volume fraction of strain-induced martensite as well as the extent of its depth. The role of the residual stress state in the martensite phase is minor. Surface strengthening expressed in terms of the microhardness in the near-surface region is very high for the medium shot peening intensity. A remarkable decrease in the near-surface microhardness as well as the presence of heavily thinned folds indicate over shot peening and surface microcracking in the case of a longer shot peening time and the corresponding higher Almen intensity.